Pendidikan Islam untuk Anak Berkebutuhan Khusus (Kajian tentang Konsep, Tanggung Jawab dan Strategi Implementasinya) - Putra, Pristian Hadi; Herningrum, Indah; Alfian, Muhammad (Prodi PAI STAI Sumatera Medan, 2021)
This study aims to analyze concept, the responsibility of Islamic education to children with special needs and its implementation strategy. This research uses library research method. Data analysis was carried out using content analysis, where each finding from the literature search was analyzed in depth to obtain uniqueness. The results of this study indicate that children with special needs should receive special attention so that they can be equal and do not feel different from other normal children. The responsibilities of Islamic education for children with special needs, namely; 1) active role of government. the government has provided, 2) strengthening the mental condition of parents, 3) adequate social support. Regarding the implementation of responsibilities, it is carried out by implementing learning strategies so that they can be optimized by making modifications (content, process, evaluation), functional, task analysis, individual learning, peer learning. In addition, inclusive education can also be carried out which provides opportunities for all students who have disabilities and have the potential for intelligence to participate in education in an educational environment together.